Cystic tumors of the pancreas. Cystadenomas and cystadenocarcinomas. Diagnosis and practical attitude - Valiñas, Roberto; Houry, Sidney; Huguier, Michel (Cirugía del Uruguay, 2004)
Report of 16 cases of cystic tumors of pancreas (CTP) consisting of 5 serous cystoadeno mas (SC), 6 mucigenous cystoadenomas (MC) and 5 cystoadenocarcinomas (CC) pertaining to 11 women and 5 men. Mean age 63 years (ranging from 44 to 89). Four of these patients were asymptomatic, 6 of them had lost between 3 and 20 kilos. One patient with a CC developed Jaundice. CTPs were diagnosed by ultrasound or CT scans. CTPs were topographed ten times at the leve/ of pancreatic head, twice in its body and tour in its tail. At end of preoperative explorations conducted for the purpose of diagnosis, CTPs went undetected in four cases. The exact diagnosis of tumor nature was made during preoperative in five cases: two SCs, one MC and two CCs. Unequivocal diagnosis was made through the histologica/ study of surgica/ specimen in eleven cases, by the existence of liver metastases in one case and by citopunture under CT in the remainder. One patient refused to be operated. Thirteen patientys were operated: in tour a cephalic duodenopancreatectomy was perfomed (1 SC and 3 CCs); in 5, tumor exeresis was performed (1 SC and 4 MCs); in 2, a distal pancreatectomy was performed (1 MC and 1 CC); and 2 underwent surgical pucture (SCs). Asymptomatic SCs may remain unoperated under surveillance, provided diagnosis be unequivocal. Al/ other cystic tumors have to be resected, either, due to the fact that there is doubt as to their nature or because ít is a symptomatic CS, or an MC or a CC. In the latter case, prognosis is better that in cases of exocrine non metastasic pancreatic cancer.